You Can’t Say That on Facebook: The NLRA’s Opprobriousness Standard and Social Media - Elizabeth Allen (Washington University Journal of Law & Policy, 2014)
In January 2013, British music retailer HMV made headlines not only for its financial woes but also for its lay-offs, publicized by a terminated employee on HMV’s Twitter account. “[T]weeting live from HR where we’re all being fired!” was Poppy Rose Cleere, the company’s Social Media Planner, who reached out to Twitter in her frustration over the layoffs. A company in a bad situation suddenly found itself in an even worse one, as it lost its ability to control its public image. The HMV incident is illustrative of the complicated relationship employers have with social media. The HMV incident is likewise illustrative of what is at stake for companies when social media is used against their interests. In response to these fears, companies have increasingly adopted and affirmed policies delineating their expectations for employees’ personal usage of social media. Employers have also disciplined employees whose social media posts have negatively portrayed the company. This Note examines the NLRA’s opprobriousness standard as applied to social media and then argues that this standard provides a strong framework for analyzing when employees’ otherwise protected concerted activity on social media should lose its protection because the speech is impermissibly opprobrious. This Note also argues that with certain modifications, this standard should be adopted by the NLRB and subsequently by courts.
Keywords: social media; HMV; Twitter/Facebook; National Labor Relations Board; NLRB; National Labor Relations Act; NLRA; the Solomon Memorandum; social media law suits/case/litigation; posting/tweeting; employer social media policies; employee privacy; employee freedom of speech; Atlantic Steel; Jefferson Standard